INSTITUTIONAL COORDINATION CHALLENGES IN FLOOD DISASTER RESPONSE: A CASE STUDY OF THE 2022 FLOODS IN DERA ISMAIL KHAN, DISTRICT, KHYBER PAKHTUNKHWA, PAKISTAN (Contemporary Journal of Social Science Review, 2026)
The aim of this study is to discuss institutional coordination challenges in flood disaster response by focusing on the flood challenges that occurred in 2022 in Dera Ismail Khan, KP, Pakistan. There is insufficient coordination between the disaster management institutions, which makes the response less effective and makes people more vulnerable to disasters in the event of a large-scale crisis situation. A qualitative case study approach has adopted. The study is based on secondary data from government reports as well as the UN and humanitarian organizations. The data is analyzed by the thematic analysis to identify the gaps in coordination and institutional weaknesses. The findings reveal broken authority between federal, provincial, and district institutions. Communication between agencies was still weak and inconsistent. Local authorities had capacity and resource limitations. Duplication of relief efforts took place in some areas, and some were neglected. Community actors were not well used. These issues altogether lowered the efficiency and timeliness of the disaster response in D.I.Khan.